Driver and Consumer Compliance with Safety Features on Online Transportation Applications - Adriansyah, Muhammad Ali; Haris, Muhammad Ichsan; Diana, Diana; Nurdin, Nurafifah (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
This study aims to describe the level of compliance of consumers and driver partners with safety features contained in online transportation applications. In addition, this study also reviewed and compared the compliance of all applicators in implementing PM 12 in 2019. Applicators that are currently operating in Indonesia are: Gojek, Grab, Maxim and InDriver. This study is a literature review. This study used documentation and survey techniques in terms of collecting research data. The sample of this study amounted to 100 respondents. The data analysis technique of this study uses a descriptive method. An important finding in this study is that all applicators already have safety features but there are still some unscrupulous drivers who do not comply and there are still some consumers who do not know the safety features. Consumers who do not know the safety feature as much as 15% and who are still confused about this feature as much as 24%. The next important finding is that the gojek applicator is the applicator with the highest level of compliance of the other three applicators. Gojek has a compliance rate of up to 94%, Grab 91%, Maxim 88% and InDriver 79% in the implementation of government regulation No. 12 of 2019.Penelitian ini bertujuan mendeskripsikan tingkat kepatuhan konsumen dan mitra pengemudi terhadap fitur keselamatan yang terdapat di aplikasi transportasi online. Selain itu, penelitian ini juga mengkaji dan membandingkan kepatuhan semua aplikator dalam menerapkan PM 12 tahun 2019. Aplikator yang saat ini sudah beroperasi di Indonesia adalah : Gojek, Grab, Maxim dan InDriver. Studi ini adalah literatur review (studi kepustakaan). Penelitian ini menggunakan teknik dokumentasi dan survey dalam hal pengumpulan data penelitian. Sampel penelitian ini berjumlah 100 orang responden. Adapun teknik analisis data dari penelitian ini menggunakan metode deskriptif. Temuan penting dalam penelitian ini adalah semua aplikator sudah memiliki fitur keselamatan namun masih ada beberapa oknum pengemudi yang tidak mematuhi serta masih ada beberapa konsumen yang belum mengetahui adanya fitur keselamatan. Konsumen yang belum mengetahui fitur keselamatan sebanyak 15% dan yang masih bingung dengan fitur ini sebanyak 24%. Temuan penting selanjutnya adalah aplikator gojek merupakan aplikator dengan tingkat kepatuhan tertinggi dari tiga aplikator lainnya. Gojek memiliki tingkat kepatuhan hingga 94%, Grab 91%, Maxim 88% dan InDriver 79% dalam penerapan peraturan pemerintah No 12 tahun 2019.